Comparison of Death Rates between COVID-19 Patients with Type 2 Diabetes Mellitus and without Type 2 Diabetes Mellitus - Widianita, Nadhila; Wibowo, Resna Murti (Muhammadiyah Medical Journal, 2023)
Background: Coronavirus Disease 2019 (COVID-19) is an acute airway infection caused by coronavirus, and one of the comorbid diseases that can increase the severity and mortality of COVID-19 is diabetes mellitus. Purposes: To compare mortality rates in COVID-19 patients with type 2 DM and those without type 2 DM at Bunda Margonda General Hospital, Depok Jawa Barat. Methods: This study is a comparative study with a cross-sectional design obtained from secondary data in the form of medical record data at Bunda Margonda Depok Hospital in January-December 2021. The collection was carried out using the total sampling technique. Data were tested using the Cross Tabulation (crosstab) test. Results: Of the 144 COVID-19 patients, 56.9% of COVID-19 patients died with type 2 DM, while 43.1% died without type 2 DM comorbidity. Based on the comparison results of the mortality rate of COVID-19 patients accompanied by Type 2 DM and those not accompanied by Type 2 DM, the P value is 0.127, which means there was no relationship between mortality rate and Type 2 DM status. The mortality rate male gender is more likely to die in COVID-19 cases with an incidence of (53.5%), while in women (46.5%). Conclusion: Patients with comorbidities are more susceptible to Covid-19, and their symptoms are divided into mild, moderate, and severe. In patients with comorbid diabetes mellitus, there will be an increased occurrence of Covid-19 disease due to decreased immune function, resulting in a longer healing time in patients with diabetes mellitus.